2018
DOI: 10.1101/405019
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experimentally reduced insulin/IGF-1 signalling in adulthood extends lifespan of parents and improves Darwinian fitness of their offspring

Abstract: 23Classical theory maintains that ageing evolves via energy trade-offs between reproduction 24 and survival leading to accumulation of unrepaired cellular damage with age. In contrast, the 25 emerging new theory postulates that ageing evolves because of deleterious late-life hyper-26 function of reproduction-promoting genes leading to excessive biosynthesis in late-life. The 27 hyper-function theory uniquely predicts that optimizing nutrient-sensing molecular signalling 28 in adulthood can simultaneously postp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(40 citation statements)
references
References 60 publications
6
31
3
Order By: Relevance
“…Specifically, it caused a shift to increased early life reproduction, improving offspring individual fitness, rather than an increase in total reproduction. Whilst an earlier study found increased total reproduction in the first generation of offspring from C. elegans parents treated with daf-2 RNAi, across N2 wild-type and two other genetic backgrounds, this was also accompanied by increased offspring fitness 20 , in agreement with our results here.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Specifically, it caused a shift to increased early life reproduction, improving offspring individual fitness, rather than an increase in total reproduction. Whilst an earlier study found increased total reproduction in the first generation of offspring from C. elegans parents treated with daf-2 RNAi, across N2 wild-type and two other genetic backgrounds, this was also accompanied by increased offspring fitness 20 , in agreement with our results here.…”
Section: Resultssupporting
confidence: 92%
“…We set out to test whether adulthood-only daf-2 RNAi, known to extend lifespan without an obvious cost to parental fecundity 19,20 , trades-off with germline maintenance, resulting in the accumulation of germline mutations and detrimental fitness effects across multiple generations. Positive effects on F1 offspring fitness observed in previous work 20 are likely driven by parental effects because we showed here that they disappear after one generation. However, we found that multigenerational downregulation of daf-2 via adulthood-only RNAi has positive effects on germline maintenance and protects mutation accumulation lines from extinction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…until the reproduction measurement was taken). The potential trade-off between number and quality of offspring is well known in the life history literature [49,50], and such inter-generational trade-offs have recently been found in Caenorhabditis nematodes [51] but are not ubiquitous [52].…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been recent questioning of this [8,15,17], and new research that addresses some key gaps may be revealing. Examining unusual patterns of senescence [3,7] may help illuminate why and how it occurs ([5]; Figure 1).…”
Section: Atypical Patterns Of Senescencementioning
confidence: 99%